Penguatan Moderasi Beragama Remaja Kampung Pancasila melalui Diseminasi ”Semai Sirama” - Mahfud, Muhammad; Mulyadi, Mulyadi; Pertiwi, Aulia Hana; Sofiyah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2025)
The present study addresses the rising phenomenon of religious intolerance and polarization among the youth, highlighting the urgent need for religious moderation as a national foundation. The current inquiry discusses a youth empowerment program centered on the dissemination of "Semai Sirama" (Nine Values of Religious Moderation) within the Kampung Pancasila environment. This article aims to instill tolerance, togetherness, and patriotism through community-based educational, creative, and collaborative activities. Employing a descriptive qualitative approach with Participatory Action Research (PAR), the investigation involved youth aged 15–21 as active participants. The program phases included value socialization, content creation training on moderation, cross-community collaborative actions, and reflections on diversity. The resulting data indicate a significant increase in the understanding and practice of religious moderation, manifested in youth-led initiatives such as digital tolerance campaigns, interfaith dialogues, and social activities rooted in Pancasila values. The findings conclude that the Semai Sirama dissemination program is an effective model for strengthening religious moderation through a contextual, participatory, and relevant approach for the contemporary generation.